Intelligent Distributed Computing XII - Del Ser, Javier; Osaba, Eneko; Bilbao, Miren Nekane; Sanchez-Medina, Javier J.; Vecchio, Massimo; Yang, Xin-She.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers a wealth of research contributions on recent advances in intelligent and distributed computing, and which present both architectural and algorithmic findings in these fields. A major focus is placed on new techniques and applications for evolutionary computation, swarm intelligence, multi-agent systems, multi-criteria optimization and Deep/Shallow machine learning models, all of which are approached as technological drivers to enable autonomous reasoning and decision-making in complex distributed environments. Part of the book is also devoted to new scheduling and resource allocation methods for distributed computing systems. The book represents the peer-reviewed proceedings of the 12th International Symposium on Intelligent Distributed Computing (IDC 2018), which was held in Bilbao, Spain, from October 15 to 17, 2018.
Part I: Main Track -- Long distance in-links for ranking enhancement -- Concept Tracking and Adaptation for Drifting Data Streams under Extreme Verification Latency -- Adversarial Sample Crafting for Time Series Classification with Elastic Similarity Measures -- Slot Co-allocation Optimization in Distributed Computing with Heterogeneous Resources -- About Designing an Observer Pattern-Based Architecture for a Multi-Objective Metaheuristic Optimization Framework -- Scalable Inference of Gene Regulatory Networks with the Spark Distributed Computing Platform -- Finding Best Compiler Options for Critical Software Using Parallel Algorithms -- Drift Detection over Non-stationary Data Streams using Evolving Spiking Neural Networks -- Part II: Energy -- A Hybrid Ensemble of Heterogeneous Regressors for Wind Speed Estimation in Wind Farms -- Bio-inspired approximation to MPPT under real irradiation conditions -- Part III: Industry -- Decision Making in Industry 4.0 Scenarios supported by Imbalanced Data Classification.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence